Академич Н.Содномын мэндэлсний 100 жилийн ойд зориулсан “Рентген шинжилгээ” олон улсын эрдэм шинжилгээний зургаадугаар хурал - Д, Болортуяа; П, Зузаан (Scientific transaction of the National University of Mongolia. Physics, 2023)
The Nuclear Research Center organized the sixth international conference on "X-ray Analysis" on August 28-30, 2023. The conference took place in a hybrid format, combining in-person and virtually. More than 60 scientists from Mongolia, Russia, Japan, the USA, Spain, Italy, India, and Argentina participated in the conference. The conference featured 24 oral presentations and 14 poster presentations covering both fundamental and applied research. These presentations delved into the latest developments in X-ray analysis, current trends, theoretical and methodological calculations, as well as applications in the fields of environment, geology, mining, substance structure, and radiation processing. This review article provides a summary of the significant and interesting presentations delivered at the conference